Assessment of Coping Skills in Pediatric Sports Medicine Patients. Issue 5 (31st May 2022) - Townsend, Tracy K.; Coene, Ryan P.; Williams, Kathryn A.; Pluhar, Emily; Ackerman, Kathryn E.; Kramer, Dennis E.; Stracciolini, Andrea; Christino, Melissa A.
Background: Psychological variables play integral roles in an athlete's response to injury recovery, and poor mental coping skills have been shown to have a negative impact. The Athletic Coping Skills Inventory-28 has been demonstrated to have predictive value in identifying pediatric patients who may be at risk for a prolonged recovery. Hypothesis/Purpose: The purpose of this study was to investigate variations in coping skills in pediatric sports medicine patients using the Athletic Coping Skills Inventory-28, and to examine correlations with the following variables: age, gender, individual vs. team sports, and time devoted to sport. Methods: This was a cross-sectional, single institution study, that assessed young sports medicine patients, ages 12-18. A one-time, voluntary, anonymous survey was utilized to assess demographics, primary sport, sport participation patterns, and the validated Athletic Coping Skills Inventory-28 (ACSI, range 0-84). Younger adolescents were considered to be ages 11-14 and older adolescents ages 15-18 for data analysis. Statistical analysis included Fischer's exact tests, t-tests, Pearson correlations, linear regression analysis, and Wilcoxon rank sum tests. Results: Of 430 eligible patients, 334 (mean±sd age 15.0±1.8 years, 64.7% female, 35.3% male) completed questionnaires, for a 78% response rate. The mean ACSI score was 50.2±10.9. No significant differences were observed in overall ACSI scores between genders. ACSI scores were higher in younger adolescents compared to older adolescents (52.4±10.5 vs 48.9±10.9, p <0.010). Team sport athletes reported higher coping skill scores than individual sport athletes (51.2±10.9 vs 47.2±10.8, p<0.001). Multivariable linear regression revealed that younger team sport athletes demonstrated higher coping skill scores compared to older team sport athletes (55.9 vs 49.8, p<0.001). Younger team sport athletes also scored higher than the younger individual sport athletes (55.9 vs 47.6 p=0.002). In addition, playing> 16 hours per week of sports adds 6.36 (95% CI: 3.14, 9.57) units to the total ACSI score compared to participants who play <11 hour per week. Conclusion: Athletic coping skills scores did not significantly differ among genders in adolescent athletes. ACSI scores were higher in younger adolescents and athletes playing team sports. Coping skill scores are also positively correlated with time devoted to playing sports.